2010
DOI: 10.1063/1.3432776
|View full text |Cite
|
Sign up to set email alerts
|

Temporal effects on spectroscopic line shapes, resolution, and sensitivity of the broad-band sum frequency generation

Abstract: Sum frequency generation (SFG) is a surface-selective spectroscopy that provides a wealth of molecular-level information on the structure and dynamics at surfaces and interfaces. This paper addresses the general issue of spectral resolution and sensitivity of the broad-band (BB) SFG that involves a spectrally narrow nonresonant (usually visible) and a BB resonant (usually infrared) laser pulses. We examine how the spectral width and temporal shape of the two pulses, and the time delay between them, relate to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 42 publications
(29 reference statements)
0
95
0
Order By: Relevance
“…As a result, the shape of the broadband VSFG spectrum depends on the delay time between the infrared and probe pulses. When the pulses overlap in time, not only can there be a significant non-resonant background, but the linewidths of vibrational features can be broadened or even shifted because only the early portion of the FID is being probed [113,114]. With typical probe pulses, the best signal intensity and spectral resolution are attained when the probe pulse arrives significantly later than the temporal peak of the infrared pulse, so that as much of the FID as possible is probed and the non-resonant background is minimised.…”
Section: Comparison Of Vsfg Spectra Obtained With Different Techniquesmentioning
confidence: 99%
“…As a result, the shape of the broadband VSFG spectrum depends on the delay time between the infrared and probe pulses. When the pulses overlap in time, not only can there be a significant non-resonant background, but the linewidths of vibrational features can be broadened or even shifted because only the early portion of the FID is being probed [113,114]. With typical probe pulses, the best signal intensity and spectral resolution are attained when the probe pulse arrives significantly later than the temporal peak of the infrared pulse, so that as much of the FID as possible is probed and the non-resonant background is minimised.…”
Section: Comparison Of Vsfg Spectra Obtained With Different Techniquesmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 8 suppress the nonresonant response of the silicon substrate. [42][43][47][48] The PPP spectrum showed three resonant vibrational modes of the terminal -CH 3 group, which are assignable to the symmetric C-H stretch (r + ) at ~2865 cm -1 , the asymmetric C-H stretch (r -) at ~2962 cm -1 , and the Fermi resonance ( ) of the r + mode with the C-H asymmetric bending overtone, at ~2933 cm -1 . 24,42,[49][50][51] The SSP spectrum, which exhibited a significant reduction in signal intensity compared with the PPP spectrum, only showed signatures ascribable to the symmetric C-H stretch (r + ) at ~2863 cm -1 and the Fermi resonance ( ) at ~2935 cm -1 .…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…We found that washing the surface with methanol several times significantly reduced the intensity. Based on the frequency, we attributed this peak to an alkyne present at the interface, although it appeared ∼30 cm −1 higher than what has been previously observed for propiolic acid by SFG 33. This peak, however, was not observed in the SFG spectra after reaction with 1‐hexyne.…”
Section: Methodsmentioning
confidence: 46%